2019
DOI: 10.1029/2018wr024463
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Inference of Flow Duration Curves Using Multioutput Neural Networks

Abstract: We develop multioutput neural network models to predict flow‐duration curves (FDCs) in 9,203 ungaged locations in the Southeastern United States for six decades between 1950 and 2009. The model architecture contains multiple response variables in the output layer that correspond to individual quantiles along the FDC. During training, predictions are made for each quantile, and a combined loss function is used for back propagation and parameter updating. The loss function accounts for the covariance between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…In most applications considered here, 95% CIs based on fitted copula models provided adequate coverage of the observations, except in the tails of the distribution ( Figures 5 and 11). It is possible that some of these tail uncertainty estimates could be improved if uncertainty from other sources was propagated forward, for instance uncertainty in the FDC estimate (see Worland et al, 2019aWorland et al, , 2019b or even measurement error at the donor sites. In addition, when the NSE values were decomposed for each model, copula-based approaches tended to have less variance error in the NSE (Figure 10).…”
Section: Benefits and Limitations To Prediction Using Copulasmentioning
confidence: 99%
“…In most applications considered here, 95% CIs based on fitted copula models provided adequate coverage of the observations, except in the tails of the distribution ( Figures 5 and 11). It is possible that some of these tail uncertainty estimates could be improved if uncertainty from other sources was propagated forward, for instance uncertainty in the FDC estimate (see Worland et al, 2019aWorland et al, , 2019b or even measurement error at the donor sites. In addition, when the NSE values were decomposed for each model, copula-based approaches tended to have less variance error in the NSE (Figure 10).…”
Section: Benefits and Limitations To Prediction Using Copulasmentioning
confidence: 99%
“…Dropout is a computationally efficient way to combine many network structures and prevent over-fitting; it adds noise and limits co-dependencies between neurons during DNN training (Srivastava et al, 2014;Goodfellow et al 2016). It involves temporarily removing randomly selected neurons during DNN training (Srivastava et al, 2014;Goodfellow et al, 2016;Worland et al 2019).…”
Section: Deep Neural Network Development Architecture and Testingmentioning
confidence: 99%
“…However, we observed that the DNN overpredicted monthly runoff in California, Texas, and Florida as indicated by large negative (i.e., < -25%) median watershed residuals (Figure 3). Future studies may use local interpretable model-agnostic explanations (LIME; Ribeiro et al, 2018) and other machine learning interpretation techniques to further explain these patterns in model residuals (e.g., Worland et al, 2019).…”
Section: Deep Neural Network Testingmentioning
confidence: 99%
See 2 more Smart Citations